Preserving Residual Renal Function in Dialysis: What We Know. Issue 3 (18th September 2014) - Patel, Nikunjkumar; Hu, Susie L.
Abstract Residual renal function confers a survival benefit among dialysis patients thought to be related to greater volume removal and solute clearance. Whether the presence of residual renal function is protective or merely a marker for better health is not clear. The basic mechanisms governing the decline or persistence of residual renal function are poorly understood and few studies have examined the role of medical therapy in its preservation. Dialysis modality, inflammatory processes often associated with comorbid diseases (including diabetes mellitus and obesity), volume dysregulation, and vitamin D deficiency are predictive of residual renal function decline. We review potential mechanisms for preservation of remaining glomerular filtration rate among chronic dialysis patients.